Constipation and clinical outcomes in peritoneal dialysis: Results from Thailand PDOPPS - Halue, Guttiga; Tharapanich, Huttaporn; Phannajit, Jeerath; Kanjanabuch, Talerngsak; Banjongjit, Athiphat; Lorvinitnun, Pichet; Sritippayawan, Suchai; Sopassathit, Wichai; Poonvivatchaikarn, Ussanee; Buranaosot, Somphon; Somboonsilp, Wanida; Wongtrakul, Pimpong; et al. (Nephrology (Carlton, Vic.), 2023)
Background Patient‐reported outcome measures (PROMs) are widely recognized as valuable predictors of clinical outcomes in peritoneal dialysis (PD). Our study aimed to explore the connections between patient‐reported constipation and clinical outcomes. Methods We assessed constipation in patients across 22 facilities participating in the Thailand Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) from 2014 to 2017. Constipation diagnosis utilized objective assessment tools such as the Bristol stool form scale (BSFS) and a self‐reported questionnaire known as the constipation severity score (CSS). The BSFS is a 7‐level scale that visually inspects feces based on texture and morphology, while the CSS measures constipation duration and severity using a 5‐point Likert scale for various factors. We employed Cox proportional hazards model regression to determine the associations between constipation and clinical outcomes, including mortality, hemodialysis (HD) transfer and peritonitis. Results Among 975 randomly selected PD patients from 22 facilities, 845 provided written informed consent, and 729 completed CSS questionnaire. Constipation was prevalent in the PD population (13%), particularly among older patients, those who were caregiver dependent, had diabetes and poorer nutritional status (indicated by lower time‐averaged serum albumin, potassium, creatinine and phosphate concentrations). Twenty‐seven percent of which experiencing symptoms of constipation for over a year. Notably, self‐reported constipation at baseline was significantly associated with a shorter time to first peritonitis and higher rates of peritonitis and death. However, no significant association was found between constipation and HD transfer after adjusting for various factors, including age, gender, PD vintage, comorbidities, shared frailty by study sites and serum albumin. Conclusion Patient‐reported constipation independently correlated with increased risks of peritonitis and all‐cause mortality, though no such correlation was observed with HD transfer. These findings underscore the need for further investigation to identify effective interventions for constipation in PD patients.